Persepsi Remaja Perokok tentang Dampak Sosial Merokok di SMK Katolik Santo Yusup Kota Blitar - Azmi Nadhira Sarwantina (STIKes Patria Husada Blitar, 2016)
Smoking habits begins at younger age, in final school period or puberty. The desire of children to try smoking is also based on their assumption that by smoking they would be accepted in some community, or considered more severe, or as a symbol of rebellion against parents. The purpose of this research was to determine the perception of Youngsters Smokers about Social Impact in Santo Yusup Catholic Vocational High School Blitar. Objective: This research used descriptive method and instruments by questionnaire. The population was male smokers and female smokers who were in Santo Yusup Catholic Vocational High School Blitar, the sample was 42 respondents, selected using total sampling technique. Result: The results showed that the perception of youngsters smokers about the social impact of smoking as much as 57% have correct perceptions and 43% have incorrect perceptions. Factors affected teenagers to have perceptions were true cognitive processed correctly about a object, subject, and certained of condition. Discussion: The recommendation from this research was expected the role of teachers to improve the knowledge and order of smoking and smoking prohibition.